2015
DOI: 10.1002/pds.3920
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following exposure to onabotulinumtoxinA

Abstract: PurposeTo evaluate pregnancy outcomes following onabotulinumtoxinA (US Food and Drug Administration pregnancy category C product) exposure using the Allergan safety database.MethodsThe Allergan Global Safety Database contains reports of onabotulinumtoxinA administration before/during pregnancy, including both prospective (reported before outcome) and retrospective (outcome already known) cases. The database was searched from 1/1/90 to 12/31/13 for eligible cases where treatment occurred during pregnancy or ≤3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 35 publications
3
44
1
3
Order By: Relevance
“…We were only able to retrieve case series and case reports, but no controlled epidemiological studies have been found. Nineteen studies are included in this review; 11 studies (1 case series [7], 1 survey [8] and 8 case reports [9][10][11][12][13][14][15][16][17]) for the therapeutic BTX-A (onabotulinumtoxinA) exposure during pregnancy included a total of 259 exposed women and 269 infants were with a known outcome (Table 1) and 8 studies (1 case series [18] and 7 case reports [19][20][21][22][23][24][25]) reporting botulism during pregnancy, included a total of 10 women (10 infants) [ Table 2]. a .Single case with four separate singleton pregnancies has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We were only able to retrieve case series and case reports, but no controlled epidemiological studies have been found. Nineteen studies are included in this review; 11 studies (1 case series [7], 1 survey [8] and 8 case reports [9][10][11][12][13][14][15][16][17]) for the therapeutic BTX-A (onabotulinumtoxinA) exposure during pregnancy included a total of 259 exposed women and 269 infants were with a known outcome (Table 1) and 8 studies (1 case series [18] and 7 case reports [19][20][21][22][23][24][25]) reporting botulism during pregnancy, included a total of 10 women (10 infants) [ Table 2]. a .Single case with four separate singleton pregnancies has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…‡ The child has been followed for 6.5 years without any neuromuscular or developmental concerns benign brain tumor identified at 13 months]. The previously identified malformations presented no distinct pattern [7]. The observed prevalence rates of spontaneous abortion and elective termination of pregnancy in the prospective part of this study were 15.1% (21/139; 95% CI, 9.4-23.1%) and 5.8% (8/139; 95% CI, 2.5-11.3%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings have not been confirmed in humans. A 24-year retrospective study of the Allergan global safety database reviewed 574 onabotulinumtoxinA treatments in pregnancy [ 18 ]. Overall the prevalence of fetal defects was comparable in both the toxin treated and general populations.…”
Section: Discussionmentioning
confidence: 99%